Functional consequences of SARS-CoV-2 infection in pregnant women, fetoplacental unit, and neonate - Carvajal, Jorge; Casanello, Paola; Toso, Alberto; Farías, Marcelo; Carrasco-Negue, Karina; Araujo, Kenny; Valero, Paola; Fuenzalida, Javiera; Solari, Caterina; Sobrevia, Luis [UNESP] (Elsevier, 2023)
The SARS-CoV-2 infection causes COVID-19 disease, characterized by acute respiratory distress syndrome, bilateral pneumonia, and organ failure. The consequences of maternal SARS-CoV-2 infection for the pregnant woman, fetus, and neonate are controversial. Thus, it is required to determine whether there is viral and non-viral vertical transmission in COVID-19. The disease caused by SARS-CoV-2 leads to functional alterations in asymptomatic and symptomatic pregnant women, the fetoplacental unit and the neonate. Several diseases of pregnancy, including COVID-19, affect the fetoplacental function, which causes in utero programming for young and adult diseases. A generalized inflammatory state and a higher risk of infection are seen in pregnant women with COVID-19. Obesity, diabetes mellitus, and hypertension may increase the vulnerability of pregnant women to infection by SARS-CoV-2. Alpha, Delta, and Omicron variants of SARS-CoV-2 show specific mutations that seem to increase the capacity of the virus to infect the pregnant woman, likely due to increasing its interaction via the virus S protein and angiotensin-converting enzyme 2 receptors. This review shows the literature addressing to what extent COVID-19 in pregnancy affects the pregnant woman, fetoplacental unit, and neonate. Prospective studies that are key in managing SARS-CoV-2 infection in pregnancy are discussed.
Keywords: Covid-19; Fetus; Neonate; Placenta; Pregnancy; Virus